Winter to summer change in vitamin D status reduces systemic inflammation and bioenergetic activity of human peripheral blood mononuclear cells - Calton, E.; Keane, Kevin; Raizel, R.; Rowlands, J.; Soares, Mario; Newsholme, Philip (Elsevier BV, 2017)
Background: Vitamin D status [25(OH)D] has recently been reported to be associated with altered cellular bioenergetic profiles of peripheral blood mononuclear cells (PBMCs). No study has tracked the seasonal variation of 25(OH)D and its putative influence on whole body energy metabolism, cellular bioenergetic profiles, inflammatory markers and clinical chemistry. Material and methods: Whole body energy metabolism and substrate utilisation were measured by indirect calorimetry. PBMCs obtained from the same subjects were isolated from whole blood, counted and freshly seeded. Bioenergetic analysis (mitochondrial stress test and glycolysis stress test) was performed using the Seahorse XFe96 flux analyser. 25(OH)D was assessed using the Architect immunoassay method. Results: 25(OH)D increased by a median (IQR) of 14.40 (20.13) nmol/L (<0.001) from winter to summer and was accompanied by significant improvements in indices of insulin sensitivity, McAuley's index (p=0.019) and quantitative insulin sensitivity check index (p=0.028). PBMC mitochondrial parameters basal respiration, non-mitochondrial respiration, ATP production, proton leak, and maximal respiration decreased in summer compared to winter. Similarly, PBMC glycolytic parameters glycolytic activity, glucose response, and glycolytic capacity were all reduced in summer compared to winter. There was also a trend for absolute resting metabolic rate (RMR) to decrease (p=0.066). Markers of systemic inflammation MCP-1, IL-6, IL-8, IL-10, and IL-12p70 decreased significantly in summer compared to winter. Participants who entered winter with a low 25(OH)D (<50 nmol/L), had the greatest alteration in bioenergetic parameters in summer, relative to those with winter 25(OH)D concentrations of 50–75 nmol/L or >75 nmol/L. The absolute change in 25(OH)D was not associated with altered bioenergetics. Conclusion: Seasonal improvements in 25(OH)D was associated with reduced systemic inflammation, PBMC bioenergetic profiles and whole body energy metabolism. These observational changes in PBMC bioenergetics were most pronounced in those who had insufficient 25(OH)D in winter. The data warrants confirmation through cause and effect study designs.